Manejo integrado de los principales insectos plaga defoliadores del cultivo de soya (Glycine max L.) - Franco Sarco, Romario Ezequiel (2020)
The protection of the soybean crop against the attack of defoliating pests is one of the cultural tasks that defines the yield of the harvest; protect the crop with control mechanisms whose environmental impact is low or moderate, would contribute to the sustainability of soy production, considering the important need to protect the foliage of plants, since these are the ones that ensure that through photosynthesis they comply its nutritive biochemical functions, it is for the reason that this research is justified. The objective of this work was to know the integrated management of the main defoliating pest insects of the soybean crop, based on this, documented results in scientific sources were reviewed, thanks to which it was possible to point out that there is information that indicates that IPM has great effectiveness, especially when among the control methods that incorporate applications with botanical products, obtained from fruits or plants that have repellent power and especially a high residual power. The acceptance and implementation of IPM depends on the interaction of numerous variables, including those of producers and the level of education of consumers, economic and social conditions, regulation, government policies, availability of IPM tools, consumer preferences ; It is advisable to design programs for the integrated management of defoliating pests of soybean cultivation, and incorporate them into field trials, this in order to compare the results with those shown in the literature consulted.